ANALYSIS OF SHARIA LIFE INSURANCE CONTRIBUTION USING MAKEHAM'S MORTALITY LAW WITH THE COST OF INSURANCE METHOD AT PT SUN LIFE MEDAN - Siregar, Rizki Kurnia; Atika, Atika; Lubis, Fauzi Arif (Jurnal Apresiasi Ekonomi, 2022)
Based on the mitigation method, insurance is divided into conventional insurance and sharia insurance. In sharia insurance, the principle of risksharing is applied. In the concept of risksharing, all participants are obliged to pay contributions to the insurance manager. This contribution consists of three elements, namely ujrah, tabarru, and tijarah. Life insurance product xxx is a discrete n-year term life insurance that includes tijarah elements in the unit link. Life insurance product xxx has three elements of contribution, namely ujrah, tabarru, and tijarah. The ujrah fund has been determined by the insurance manager and is explained in detail in the policy agreement. The tijarah fund depends on the investment level assumption chosen by the prospective insurance participant. In addition to these two elements, the insurance manager must calculate tabarru to pay the insurance participant's claim. In this study, an estimate will be made for the gross contribution of the tabarru fund. To estimate the gross contribution of tabarru funds, the Cost of Insurance (COI) method is used which involves the variable ?? (the probability of death of a person aged ? years obtained from the mortality table), discount factor, and assumptions of management fees. The Gompertz mortality law approach is used to refine the mortality table. The results are in the form of a table of gross contributions of tabarru funds for prospective male and female participants with an assumption of insurance compensation of Rp. 250,000,000 for the age range of 1-111 years with nine combinations of three investment return assumptions and three management fees that can be chosen by prospective insurance participants.Keywords: sharia insurance, contribution, COI